Problematic Analysis of Cash Waqf Management in West Sumatera through Analytic Network Process (ANP) Approach - Nil Firdaus; Amiur Nuruddin; Fifi Hasmawati (Budapest International Research and Critics University, 2019)
Implementation of good governance in cash waqf institutions is a must. But in its implementation in West Sumatra there are still various problems in governance which have an impact on not maximizing the collection of cash waqf. Through the Analytic Network Process (ANP) approach this study tries to answer several questions: (1) what are the priority issues of cash waqf management, (2) What are the priority solutions for cash waqf management and (3) what are the cash waqf management strategy in West Sumatra. The results showed that the priority of problems in cash waqf management in West Sumatra in priority order were Human Resources (0.371), regulation (0.243), accountability (0.200) and products (0.184) with the rater agreement (W: 0.377). Priority results solutions with Human Resource solution sequences (0,367), regulator solutions (0.267), product solutions (0.183) and accountability (0.181). The results of the rater agreement with the value (0.348). While the results of the strategy in the order of collaboration with the Tungku Tigo Sajarangan are the top priority with a value (0.366), public education about cash waqf (0.324) and nazhir guidance and mauquf alaih (0.308). The rater agreement value is equal to (W: 0.111).